The impact of institutional features on R&D in business enterprise sector and sustainable growth - Milutin Ješić; Miomir Jakšić (Journal of Central Banking Theory and Practice, 2020)
The main goal of our study is to theoretically and empirically contribute to the analysis of relation between institutional features and R&D in business enterprise sector and consequently on sustainable economic growth. We exploited the available measures of institutional quality from World Government Indicators of World Bank and data on R&D in business enterprise sector. We employed First-Differencing GMM method to estimate the model on the balanced panel data including the following European countries: Bulgaria, Croatia, the Czech Republic, Hungary, Poland, Romania, Serbia and the Slovak Republic, for the time span of 2007-2017. The institutional features are statistically significant factor of R&D in business enterprise sector. We found that Government effectiveness and Control of corruption in particular are very important in supporting the R&D. These measures of institutional quality are key institutional determinants of R&D in business enterprise sector. R&D in business enterprise sector is one of the crucial parts of the overall R&D, and therefore policymakers have to develop favourable conditions for those activities in private firms. Institutional features should be an important variable in explanation of R&D intensity. The presented analysis empirically contributes to the body of knowledge on determinants of R&D for European countries that have to develop their institutions further in order to grow sustainably. This study is using contemporary methods for testing the underlying problem.
Keywords: O31; O38; O43; 330; R&D in business enterprise sector; institutions; sustainable growth; government effectiveness; control of corruption